Teknik Balon Ganda Untuk Ablasi Septum Miokardium Transluminal Perkutan Pada Kardiomiopati Hipertrofik - Haryadi Adi; Yoga Yuniadi; Dicky A Hanafy (The Indonesian Heart Association, 2011)
Percutaneous transluminalseptal myocardial ablation (PTSMA), has been a standard treatment of hypertrophic cardiomyopathy (HCM). Rarely, special technique of PTSMA needed for complicated HCM case with collateral of target artery (septal perforator) into distal left anterior descending. To overcome such problem, a case of double balloon technique during PTSMA will be elaborated.